Enhancing Employee Performance in The Public Sector: The Role of Human Resource Competence and Organizational Communication with Evidence from Selayar Islands Regency - Muh. Alim; Muhammad Rusydi; Muchriady Muchran (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to examine the influence of technical guidance, human resource (HR) competence, and organizational communication on employee performance at the Secretariat of the Regional House of Representatives (DPRD) of the Selayar Islands Regency using a quantitative survey approach with 80 respondents; data were collected through questionnaires and analyzed using multiple linear regression with prior validity, reliability, and classical assumption tests to ensure model accuracy. The findings reveal that HR competence and organizational communication have a positive and significant effect on employee performance, while technical guidance does not show a significant influence; moreover, organizational communication is identified as the most dominant variable. The model demonstrates strong explanatory power with an R² value of 0.871, indicating that 87.1% of performance variation is explained by the independent variables. These results emphasize the critical role of effective communication and competent human resources in improving organizational performance, while highlighting the need to redesign training programs to better align with job-specific demands in the public sector.